(untitled) (IIUC Business Review, 2026)
This study focuses the Propensity Score Adjustment (PSA) technique for reducing bias in web panel surveys. Web panel surveys have become increasingly popular in recent years due to their convenience, time and cost-effectiveness. However, they are prone to various sources of bias, including nonresponse bias, selection bias, and measurement bias. PSA is a statistical technique that can be used to adjust for these biases by weighting the data based on a participant’s propensity score, which is a measure of their likelihood of being included in the sample. The study’s application involved collecting data through web panel surveys on "Usage of social networking sites in education: a case study on International Islamic University Chittagong (IIUC)". The PSA technique was employed to adjust for potential selection bias that may arise from the non-random selection of participants in the web panel. The study concludes by highlighting the efficacy of utilizing PSA in web panel surveys and offering recommendations for its implementation. IIUC Business Review, Vol.-12, Issue-1, December 2023, pp. 25-46